1997
DOI: 10.1159/000139529
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Reduces Myocardial Contractility in Isoproterenol-Stimulated Rat Hearts by a Mechanism Independent of Cyclic GMP or Cyclic AMP

Abstract: Nitric oxide has been shown to decrease myocardial contractility and O2 consumption. This study was designed to evaluate the hypothesis that nitric oxide-mediated increases in cyclic GMP require elevated cyclic AMP to produce cardiac depression. Using isolated, Langendorff-perfused rat hearts, we determined the effects of intracoronary nitroprusside (NP, 1 and 10 mM) in the absence and presence of isoproterenol (ISO, 10–8 M) on cardiac function, O2 consumption, cyclic GMP and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(63 reference statements)
0
5
1
Order By: Relevance
“…This assumption is supported by the fact that 8-Br-cGMP, a known permeable and structural cGMP analogue, produced an inhibition of the contractile response elicited by isoprenaline only in WKY rat strips. Although NO may regulate cardiac contraction in a cGMP-dependent (Kelly et al, 1996;Balligand & Cannon, 1997) or independent manner (Weiss, Sadoff, Scholz & Klabunde, 1997), our results suggest that, in our experimental conditions, NO modulates negatively the isoprenaline-induced positive inotropic effect in strips from WKY rats through guanylyl cyclase activation and generation of cGMP. Increases in intracellular cGMP may activate cGMP-dependent protein kinases, which decrease calcium current through regulation of L-type calcium channels (Mery et al, 1991;Wahler & Dollinger, 1995) or decrease cardiac myofilament sensitivity to calcium through phosphorylation of troponin I Gauthier et al, 1998), and cGMP-stimulated phosphodiesterases (Beavo, 1995), which decrease cAMP levels (Mery et al, 1993).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This assumption is supported by the fact that 8-Br-cGMP, a known permeable and structural cGMP analogue, produced an inhibition of the contractile response elicited by isoprenaline only in WKY rat strips. Although NO may regulate cardiac contraction in a cGMP-dependent (Kelly et al, 1996;Balligand & Cannon, 1997) or independent manner (Weiss, Sadoff, Scholz & Klabunde, 1997), our results suggest that, in our experimental conditions, NO modulates negatively the isoprenaline-induced positive inotropic effect in strips from WKY rats through guanylyl cyclase activation and generation of cGMP. Increases in intracellular cGMP may activate cGMP-dependent protein kinases, which decrease calcium current through regulation of L-type calcium channels (Mery et al, 1991;Wahler & Dollinger, 1995) or decrease cardiac myofilament sensitivity to calcium through phosphorylation of troponin I Gauthier et al, 1998), and cGMP-stimulated phosphodiesterases (Beavo, 1995), which decrease cAMP levels (Mery et al, 1993).…”
Section: Discussioncontrasting
confidence: 55%
“…The physiological relevance of the endogenous NO on myocardial contractility regulation has repeatedly been a matter of controversy. Although it is likely that NO generation per se does not alter cardiodynamics (Weyrich et al, 1994), there is increasingly emerging evidence that endogenous NO mediates the myocardial contractile response to various other agents (Joe et al, 1998;Kotchi et al, 1998;Weiss et al, 1997;Ebihara & Karamzyn, 1996;Flesch et al, 1997). In this way, a recent study has demonstrated that NO as well as guanylate cyclase inhibitors attenuate b-adrenoceptor-mediated cardiac responses supporting the concept that NO serves as an endogenous regulator of b-adrenoceptor-mediated effects of catecholamines in the heart (Ebihara & Karamzyn, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are reports that NO has a cardiodepressive action after ischemia -reperfusion. 29,30 However, whether NO acts as a cardiodepressant agent or as a cardioprotective agent depends on the level of oxidative stress in the myocardium. Because NO has an extremely high affinity for superoxide radicals, it rapidly lose its biological activity through reaction with them.…”
Section: Discussionmentioning
confidence: 99%
“…NO has been reported to mediate both early-and latephase ischemic preconditioning in rabbits [6,21], suggesting that NO is a common mediator of simvastatin's effect and ischemic preconditioning to reduce infarct size. Although multiple reports have demonstrated that NO has a cardiodepressive action after ischemia-reperfusion [22,23], whether NO functions as a cardiodepressant or cardioprotective agent depends on the level of oxidative stress in the myocardium. If the increased production of NO is balanced by a similar increase in oxygen radical formation, NO will exert beneficial effects.…”
Section: Discussionmentioning
confidence: 99%